METODE EVERYONE IS TEACHER HERE PADA KETERAMPILAN MEMBACA BAHASA JERMAN PESERTA DIDIK SMA - PUTRI B R I, DINASTI (LATERNE, 2017)
The one of four language skills that must be mastered by learners is reading. Reading is a process that undertaken reader to obtain information (tarigan;2008). Reading is an activity to understand something meaningful and interrelated with the aim to build a sense of other concepts that already exist in the literature (Ehrlers;1992). A teacher need to implement a variety of methods appropriate, fun and can help learners to improve reading comprehension skills, especially in the German languange. One of many methode that can be applied is a Everyone is teacher here method. The problem of this research is how the learning outcomes of reading skill of the German language learners in second semester grade X mipa 1 Driyorejo 1 Senior High School using Everyone is teacher here method. This study aims to identify and describe the learning outcomes of reading skill German high school student of class X of SMAN 1 Driyorejo the second half through the implementation methods everyone is teacher here. this research is a field whose data comes from the students of class X of Science 1 SMAN 1 Driyorejo. Data of this research is the study of students seen from the test about their reading skills German. The instrument of this research is a test instrument in the form of matter taken from the book Kontakte nontes Deustch and instruments in the form of systematic observation sheet in the form of checklists. The study was conducted during 4 meetings, application of the method performed at the second meeting until the fourth meeting. Results obtained data adjusted to the minimum completeness criteria German and analyzed based on the theory of reading skills criteria b Bolton, then be deduced. The result showed that the Everyone is teacher here method can be used as an alternative method of learning the German language reading skills. It is seen from the increase in reading skills learning outcomes German language learners school class X SMAN 1 Driyorejo using Everyone is teacher here method. Keywords: reading comprehension skills, Everyone is Teacher Here method.